2020
DOI: 10.1002/jso.25929
|View full text |Cite
|
Sign up to set email alerts
|

The impact of wait times on oncological outcome in high‐risk patients with endometrial cancer

Abstract: Objective To evaluate the impact of surgical wait times on outcome of patients with grade 3 endometrial cancer. Methods All consecutive patients surgically treated for grade 3 endometrial cancer between 2007 and 2015 were included. Patients were divided into two groups based on the time interval between endometrial biopsy and surgery: wait time from biopsy to surgery ≤12 weeks (84 days) vs more than 12 weeks. Survival analyses were conducted using log‐rank tests and Cox proportional hazards models. Results A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 19 publications
(23 reference statements)
0
14
1
Order By: Relevance
“…The absence of this logical negative association may be related to the higher prevalence of Type I carcinomas, with a slow evolution and better prognosis. Other similar studies considered that some cases were not endometrial carcinoma when symptoms started but it then evolved into cancer during the wait [11,12,14]. Despite these explanations, it cannot be overlooked that 46%-56% of diagnoses were made more than six months after symptom onset, even though the cases evaluated came from a developed region of Brazil.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The absence of this logical negative association may be related to the higher prevalence of Type I carcinomas, with a slow evolution and better prognosis. Other similar studies considered that some cases were not endometrial carcinoma when symptoms started but it then evolved into cancer during the wait [11,12,14]. Despite these explanations, it cannot be overlooked that 46%-56% of diagnoses were made more than six months after symptom onset, even though the cases evaluated came from a developed region of Brazil.…”
Section: Discussionmentioning
confidence: 97%
“…Aspiration biopsies were rarely used for diagnoses, somewhat more in Type II (24% vs. 11% for Type I), perhaps due to the greater severity of symptoms at presentation requiring a more urgent diagnosis and treatment. The low proportion of aspiration biopsies used, a simple method for diagnosis of symptomatic women, although not accessible in the Brazilian Public Health System, can justify in part the long waiting time observed for the diagnosis, greater than eight months on average, when compared to the few weeks usually reported for other countries [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Other studies have shown that a longer time to surgery did not increase the risk of receipt of adjuvant chemotherapy for low-risk endometrial cancers and did not affect survival for patients with high-risk tumors. [24][25][26] Specifically looking at nonendometrioid histology, Nica and colleagues 27 found that delays of more than 45 days for surgery did result in decreased overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated no consistent association between time to diagnosis and ovarian cancer survival 11 13 15 22. In endometrial and cervical cancer, data are likewise mixed on whether delayed treatment is associated with worse survival 23–26. Outside of gynecologic oncology, delayed treatment has been shown to worsen survival in some sites,27 28 with no difference in others 29 30…”
Section: Discussionmentioning
confidence: 99%